POLA GEJALA KESULITAN BELAJAR SISWA SMA PADA PEMBELAJARAN DARING MASA PANDEMI COVID 19 - Yanti Nur'amalia, - (2021)
This study aims to produce an overview of the pattern of student learning difficulties when learning online during the Covid-19 pandemic. The scope studied in this study includes an overview of the types of student learning difficulties when learning online based on aspects and gender. This study uses a quantitative approach with a survey method. The type of survey used is Cross-Sectional Survey Design. The study was conducted on 100 samples of high school students in class X at Al Qona'ah High School Bandung. Collecting data using a questionnaire regarding learning difficulties. The results of this study found that the symptoms of student learning difficulties were difficulties in understanding the subject matter, making conclusions about the subject matter, obtaining low scores on the tasks given by the teacher to students. These findings can be used as an initial identification of students' learning difficulties during online learning so that improvement programs can be carried out.